TiO2 nanoparticles negatively impact the bioavailability and antioxidant activity of tea polyphenols. (1st March 2022) - Li, Qian; Liu, Lu; Duan, Mengran; Chen, Xiaoqiang; Li, Jing; Zhao, Tiantian; Fu, Yinxin; Julian McClements, David; Huang, Jialu; Lin, Hongyi; Shi, Jinglan
Graphical abstract: Highlights: Impacts of TiO2 NPs on the contents and antioxidant activity of TP were studied. TiO2 NPs reduced the total and individual TP contents in a dose-dependent manner. The polyphenol-TiO2 NPs complexes were stable during in vitro digestion. 0.5% TiO2 NPs markedly reduced the bioavailability and antioxidant activity of TP. Abstract: This study was to investigate the influence of TiO2 nanoparticles (NPs) on the stability, bioavailability, and antioxidant activity of co-ingested tea polyphenols extract using an in vitro digestion model. The tea polyphenol contents decreased significantly after addition of 0.5 % (w/w) TiO2 NPs. The gallocatechin gallate level decreased the most, changing from 101.9 to 27.2 µg/mL (about 73.3%). The TiO2 NPs also reduced the bioavailability of the tea polyphenols in a dose-dependent manner, which was ascribed to the formation of large polyphenol-TiO2 NP complex aggregates that could not pass through the pores in the dialysis tube used to simulate the gut wall. Additionally, the TiO2 NPs decreased the antioxidant activity of the tea polyphenols within the simulated gastrointestinal tract. In summary, our results show that high levels of TiO2 NPs (but within the current legal limits in many countries) may negatively impact the bioavailability and bioactivity of polyphenols in foods.